Infliximab therapy increases the frequency of circulating CD16+ monocytes and modifies macrophage cytokine response to bacterial infection. (September 2014) - Nazareth, N.; Magro, F.; Silva, J.; Duro, M.; Gracio, D.; Coelho, R.; Appelberg, R.; Macedo, G.; Sarmento, A.
Summary Crohn's disease (CD) has been correlated with altered macrophage response to microorganisms. Considering the efficacy of infliximab treatment on CD remission, we investigated infliximab effects on circulating monocyte subsets and on macrophage cytokine response to bacteria. Human peripheral blood monocyte‐derived macrophages were obtained from CD patients, treated or not with infliximab. Macrophages were infected with Escherichia coli, Enterococcus faecalis, Mycobacterium avium subsp. paratuberculosis (MAP) or M. avium subsp avium, and cytokine levels [tumour necrosis factor (TNF) and interleukin (IL)‐10] were evaluated at different time‐points. To evaluate infliximab‐dependent effects on monocyte subsets, we studied CD14 and CD16 expression by peripheral blood monocytes before and after different infliximab administrations. We also investigated TNF secretion by macrophages obtained from CD16+ and CD16− monocytes and the frequency of TNF+ cells among CD16+ and CD16− monocyte‐derived macrophages from CD patients. Infliximab treatment resulted in elevated TNF and IL‐10 macrophage response to bacteria. An infliximab‐dependent increase in the frequency of circulating CD16+ monocytes (particularly the CD14++CD16+ subset) was also observed (before infliximab: 4·65 ± 0·58%; after three administrations: 10·68 ± 2·23%). In response to MAP infection, macrophages obtained from CD16+ monocytes were higher TNF producers and CD16+ macrophages from infliximab‐treated CD patients showed increased frequency of TNF+ cells. In conclusion, infliximab treatment increased the TNF production of CD macrophages in response to bacteria, which seemed to depend upon enrichment of CD16+ circulating monocytes, particularly of the CD14++CD16+ subset. Infliximab treatment of CD patients also resulted in increased macrophage IL‐10 production in response to bacteria, suggesting an infliximab‐induced shift to M2 macrophages.